Answer:
f(x-1) = (3/4)x² - (5/2)x + 7/4
Step-by-step explanation:
To find f(x-1), we need to replace x by (x-1) on the equation of f(x), so
![\begin{gathered} f(x)=(3)/(4)x^2-x \\ f(x-1)=(3)/(4)(x-1)^2-(x-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/slwxm3rbrlqhwia5p4hbg5p12uiujix83e.png)
Then, we can simplify the polynomial
![\begin{gathered} f(x_{}-1)=(3)/(4)(x^2-2x+1)-x+1 \\ f(x-1)=(3)/(4)x^2-(3)/(4)(2x)+(3)/(4)-x+1 \\ f(x-1)=(3)/(4)x^2-(3)/(2)x-x+(3)/(4)+1 \\ f(x-1)=(3)/(4)x^2-(5)/(2)x+(7)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d5dqpm7us6flf85ytvz3rb9g48t1gprv9m.png)
Therefore, the simplified polynomial for f(x-1) is
f(x-1) = (3/4)x² - (5/2)x + 7/4